THE EFFECT OF CAPITAL STRUCTURE AND CREDIT TURNOVER ON THE FINANCIAL PERFORMANCE OF COOPERATIVES IN BANGLI REGENCY - I Kadek Dwi Mahendra; Ni Ketut Lely Aryani Merkusiwati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The financial performance of cooperatives is one of the key indicators for assessing the effectiveness and efficiency of organizational resource management, particularly amid intense business competition and post-pandemic challenges. This study aims to analyze the effect of capital structure and credit turnover on the financial performance of cooperatives in Bangli Regency. The research population includes all cooperatives in Bangli Regency, with a purposive sampling technique resulting in 43 cooperatives as the study sample. Thus, the total number of observations is 86 (43 cooperatives × 2 years) for the fiscal years 2023–2024. The research data were obtained from audited financial reports presented at the Annual Members’ Meeting (RAT). Data analysis was conducted using multiple linear regression to test both the simultaneous and partial effects of the independent variables on the dependent variable. The results show that capital structure has a positive and significant effect on the financial performance of cooperatives. Meanwhile, credit turnover also exerts a significant effect, although it may be negative if credit risk management is not properly handled. These findings contribute theoretically to the development of financial accounting literature and offer practical implications for cooperative management in formulating more optimal funding and credit management policies